Growth curves for Macrobrachium rosenbergii in semi-intensive culture in Brazil - Sampaio, Célia M. S. [UNESP]; Valenti, Wagner Cotroni [UNESP] (Wiley, 1996)
Four 0.02-ha earthen ponds at the UNESP Aquaculture Center, Jaboticabal, São Paulo, Brazil, were stocked with newly metamorphosed Macrobrachium rosenbergii post-larvae at 1.5 animals/m2. After 8 mo, prawn density at harvest ranged from 0.3/ m2 to 0.8/m2. Growth curves were determined for each population using von Bertalanffy growth functions. Asymptotic maximum length and asymptotic maximum weight increased as final population size decreased indicating that a strong density effect on prawn growth occurs in semi-intensive culture, even when populational density varies within a small range of less than 1 animal/m2.